Peroral endoscopic myotomy for symptomatic blown-out myotomy following previous myotomy for achalasia - Zhang, Zhao-Chao; Xu, Jia-Qi; Pan, Hai-Ting; Liu, Xin-Yang; Chen, Shi-Yao; Zhong, Yun-Shi; Zhang, Yi-Qun; Ma, Li-Li; Hu, Jian-Wei; Cai, Ming-Yan; Qin, Wen-Zheng; Li, Quan-Lin; Chen, Wei-Feng; Zhou, Ping-Hong (Endoscopy, 2025)
Blown-out myotomy (BOM) may impair the discharge of esophageal contents, leading to recurrent symptoms following myotomy. This study aimed to evaluate the safety and effectiveness of salvage peroral endoscopic myotomy (POEM) for symptomatic BOM.Between August 2011 and August 2022, 77 patients with recurrent achalasia with BOM and 168 with recurrent achalasia without BOM underwent POEM and were retrospectively enrolled. Operation-related parameters were compared between the two groups.Salvage POEM was performed in patients with symptomatic BOM, with a mean procedure duration of 60.8 minutes. The mean hospital stay was 3.2 days. Procedure-related adverse events included 16 cases (20.8%) of Type I mucosal injury, 3 cases (3.9%) of Type II mucosal injury, 5 cases (6.5%) of pneumothorax, 2 cases (2.6%) of emphysema, and 2 cases (2.6%) of pneumoperitoneum. Three patients (3.9%) experienced major adverse events. No statistically significant differences were found between the two groups in the incidence of mucosal injury, gas-related adverse events, and major adverse events. Clinical success was equivalent between the two groups at the 2-year follow-up (85.7% vs. 92.3%; P = 0.16).Based on this study, POEM could be considered as an effective treatment option for patients with symptomatic BOM.